2021
DOI: 10.1016/s1473-3099(20)30598-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparing accuracy of lipoarabinomannan urine tests for diagnosis of pulmonary tuberculosis in children from four African countries: a cross-sectional study

Abstract: We searched PubMed Central for all studies or reports of lipoarabinomannan for the diagnosis of pulmonary tuberculosis in children. We used search terms "pulmonary tuberculosis" OR "ptb" AND "child" OR "infant" OR "adolescent" AND "lipoarabinomannan" OR "lam" AND "urine", up to Mar 9, 2020. No language restrictions were applied. Our search returned five relevant publications that included children below 15 years undergoing LAM testing of urine for diagnosis of pulmonary tuberculous using AlereLAM. None of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
49
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 19 publications
1
49
0
Order By: Relevance
“…Children have a high risk of developing disseminated forms of TB, and the hematogenous and lymphatic spread of M. tuberculosis is likely to result in high amounts of LAM in urine [ 2 , 9 ]. However, few studies have reported the performance of FujiLAM in children [ 27 , 28 ]. A multicentre study in four African countries reported a relatively high sensitivity of 67.5% in HIV-negative children [ 28 ], but a cohort study in South Africa reported a lower sensitivity of 38.8% [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Children have a high risk of developing disseminated forms of TB, and the hematogenous and lymphatic spread of M. tuberculosis is likely to result in high amounts of LAM in urine [ 2 , 9 ]. However, few studies have reported the performance of FujiLAM in children [ 27 , 28 ]. A multicentre study in four African countries reported a relatively high sensitivity of 67.5% in HIV-negative children [ 28 ], but a cohort study in South Africa reported a lower sensitivity of 38.8% [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have reported the performance of FujiLAM in children [ 27 , 28 ]. A multicentre study in four African countries reported a relatively high sensitivity of 67.5% in HIV-negative children [ 28 ], but a cohort study in South Africa reported a lower sensitivity of 38.8% [ 27 ]. The authors concluded that the differences in their results may have been due to the severity of the TB episodes, and that some of the studies included a high proportion of malnourished children [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While Fuji-LAM and Determine had comparable specificity (87.8% and 83.8%), sensitivity was notably higher with Fuji-LAM (64.9% versus 30.7%) using reference standards Xpert Ultra or MTB culture. Interestingly, in this study, Fuji-LAM sensitivity was higher among HIV-negative than HIV-positive children [ 38 ]. Together with these recent reports, our findings emphasize the potential value of LAM-testing for diagnosing TB in HIV-negative, SAM children.…”
Section: Discussionmentioning
confidence: 93%
“…Importantly, the sensitivity of both FujiLAM and Determine were notably higher among malnourished children (62% vs 31% FujiLAM, 67% vs 46% Determine-LAM) [ 21 ]. A second study compared Determine and Fuji-LAM among children with presumptive TB (15% HIV-positive) in four African countries [ 38 ]. While Fuji-LAM and Determine had comparable specificity (87.8% and 83.8%), sensitivity was notably higher with Fuji-LAM (64.9% versus 30.7%) using reference standards Xpert Ultra or MTB culture.…”
Section: Discussionmentioning
confidence: 99%